Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian (Studi Kasus Pada Konsumen Alfamart Klambir Lima Raya Medan) - Gitari Aristo Putri; Nahar Maganda Saragih (Student Research Journal, 2023)
In this study aims to determine the effect of the variable Price and Product Quality Variables on Purchasing Decisions. The research method in this study was to use quantitative with a population of 3,005 people and the number of samples used in this study were 97 respondents using the slovin formula. The analysis technique used in this study uses descriptive statistical tests, classical assumption tests, hypothesis testing and also the coefficient of determination. The results of this study are that partially it can be concluded that H1 is rejected, which means that partially the price does not have a positive and significant influence on purchasing decisions. then on the product quality variable partially Product Quality has a positive and significant influence on Purchasing Decisions this is because the provisions test in the T test is Tcount must be greater than Ttable. Simultaneously, the results of this study show that the variable price (X1) and product quality (X2) together have a positive and significant effect on purchasing decisions for consumers at PT. Alfamart.